Chances or Choices? How We Think Parenthood Shapes Our Own and Others' Careers - Morien El Haj; Axana Dalle; Elsy Verhofstadt; Luc Van Ootegem; Stijn Baert (Institute of Labor Economics (IZA), 2025)
This letter contributes to the literature on gender disparities in professional life by exploring how men and women perceive the impact of parenthood on career outcomes. It does so through the lens of perceived employer-given opportunities ('chances') and perceived own career-related behaviour ('choices'). We focus on how employees perceive this impact not only on their own careers but also on those of other parents. To this end, we survey a probability sample of 1,060 employees in Belgium. We find that fathers perceive a less negative impact of parenthood on their own careers than mothers do, in terms of both chances and choices. Additionally, mothers perceive greater career penalties for other mothers than they report for themselves. These insights are valuable in understanding how self-fulfilling prophecies may shape parents' careers.
Keywords: C83; J13; J17; J71; 330; discrimination; fatherhood; motherhood; career; survey